2002
DOI: 10.1097/00004647-200204000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caspase-3 Activation in Cerebral Ischemia-Induced Neurodegeneration in Adult and Neonatal Brain

Abstract: These studies have addressed the role of caspase-3 activation in neuronal death after cerebral ischemia in different animal models. The authors were unable to show activation of procaspase-3 measured as an induction of DEVDase (Asp-Glu-Val-Asp) activity after focal or transient forebrain ischemia in rats. DEVDase activity could not be induced in the cytosolic fraction of the brain tissue obtained from these animals by exogenous cytochrome c/dATP and Ca2+. However, the addition of granzyme B to these cytosolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
123
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 51 publications
12
123
0
4
Order By: Relevance
“…Immunostaining of active caspase-3 showed very few positive cells in most regions of the adult brain, indicating that caspase-3-mediated neuronal death does not play a major role in the mature brain after HI, in accordance with earlier findings. 1,27 In support of our findings, Pohl et al 45 found a marked decrease with age in the extent of distant, apoptosis-related cell death after traumatic brain injury.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Immunostaining of active caspase-3 showed very few positive cells in most regions of the adult brain, indicating that caspase-3-mediated neuronal death does not play a major role in the mature brain after HI, in accordance with earlier findings. 1,27 In support of our findings, Pohl et al 45 found a marked decrease with age in the extent of distant, apoptosis-related cell death after traumatic brain injury.…”
Section: Discussionsupporting
confidence: 88%
“…26 It seems clear that, depending on the developmental level of the brain at the time of injury, different cell types and regions will be injured, at different rates, and different mechanisms of injury will be activated. 1,3,22,27,28 Understanding the nature of cell death after HI at different developmental stages is essential to be able to choose effective therapeutic targets, 29,30 and since these vary during development, prevention and treatment of brain injury need to be adjusted accordingly. To better understand the mechanisms and developmental variations of HI neuronal cell death, we developed a mouse model where a similar extent of injury could be achieved by adjusting the duration of the hypoxia time, thereby enabling us to study the relative contribution of different mechanisms at different ages.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tchameni et al (2011) also reported significantly greater amino acid synthesis in fungi-inoculated plants compared to control plants. Sesamin and sesamolin are major lignans in sesame plants, and these exhibit their antioxidant activity against pathogen infection (Jeng & Hou 2005) by suppressing reactive oxygen species generation and mitogen-activated protein kinases (Gill et al 2002). In the present study, both sesamin and sesamolin content were higher in the fungi-associated plants than in the control plants (Figure 7).…”
Section: Effect Of Fungal Treatments On the Primary And Secondary Metsupporting
confidence: 47%
“…Inhibition of apoptotic effectors downstream from death receptors, such as caspases, has resulted only in partial protection. [99][100][101] It has been suggested that autophagy may precede apoptosis after neonatal brain ischemia. 102 Importantly, failure to complete apoptosis results in programmed cell necrosis (also known as necroptosis), an intermediate form of cell death that exhibits features of both necrosis and apoptosis.…”
Section: Modes Of Cell Death In the Injured Neonatal Brainmentioning
confidence: 99%